The role of human resources in processes of portuguese firms’ RD&I certification and development - Gomes, Sérgio; Braga, Vítor; Braga, Alexandra (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Innovation is seen as a competitive advantage that many companies use to ensure the continuity and success of your business. NP 4457:2007 is the Portuguese norm that supports management, based on a model of innovation backed up by interfaces and interaction between technical/scientific knowledge, its specific mechanisms and the overall society. Our paper aims to analyse innovation activities and the involvement of human resources in Portuguese firms certified by NP4457 and associated to the implementation of Research, Development, and Innovation (RD&I) management systems. We have collected the data through IPAC’s database, using a survey administered to all firms. Our results suggest the existence of a Human Resources (HR) involvement policy, customers and suppliers. The involvement of stakeholders with innovation activities results of its acceptance as a mechanism able to generate wealth, with benefits for both firms and the community.